Fabrication and composition control of porous ZnO-TiO2 binary oxide thin films via a sparking method - Kumpika T. (2017)
© 2017 Elsevier GmbH ZnO-TiO 2 binary oxide thin films have been deposited on quartz substrate using sparking of zinc and titanium electrodes. The composition ratio of zinc to titanium in the sparked films is inverse correlated with the emission intensity of Zn/Ti ratio during high voltage discharges across the gap of zinc anode – titanium cathode tips. Interestingly, it exhibited a direct correlation for zinc cathode – titanium anode experiment. Moreover, the Zn/Ti atomic ratio in the deposited films is correlated with Zn/Ti electrode mass loss rate ratio. Meanwhile, the mass loss rate from a metal wire corresponds to an amount of energy required to melt the metal electrodes. Furthermore, structural and optical properties of the as-deposited and the annealed films were investigated. The sparking process is a versatile nano-coating process for metal oxides as well as their binary compounds.